PHYTOPLANKTON SPECIES COMPOSITION IN SEAWATER AND TISSUE OF GREEN MUSSELS (PERNA VIRIDIS), AT KALI BARU-CILINCING, NORTH JAKARTA - Widiarti, Riani; Yasman, -; Mulyani, -; Kurnia, Nita; Razi, Fachrul (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2013)
Species composition and abundances of phytoplankton in the shellfish farming area in Jakarta Bay, Kali Baru-Cilincing, were examined in order to identify harmful algae species. Phytoplankton contained in the shellfish was also observed to detect the presence of toxic species, as well as the phycotoxin contained inÂ visceral of green mussel (Perna viridis) collected from the farming area using brine shrimp lethality test (BSLT). We detected the presence ofÂ Alexandrium spp. (PSP causing species), Dinophysis caudata, D. miles and D. rotundata (DSP causing species), and Pseudo-nitzschia spp. (ASP causing species). The last mentioned species was also detected in thestomach content of green mussel. The toxicity of green mussels tested was recorded LC 50 â?¤ 1,000 ppm and indicatedthe presence of an active compound in the green mussel viscera. Meanwhile, preliminary PSP test of shellfish did not showed any toxin.